Determination of abundance and symbiotic effectiveness of native rhizobia nodulating soybean and other legumes in Rwanda - Nzeyimana, F.; Onwonga, R.N.; Ayuke, F.; Chemining'wa, G.N.; Nabahungu, N.L.; Bigirimana, J.; Josiane, U.K.N. (Wiley, 2024)
Rhizobia diversity in the rhizosphere is one of the key promoters of biological nitrogen fixation between host legumes and microsymbionts, although related complex interaction may depend on various factors. This research was intended to assess the abundance of indigenous rhizobia isolates under various soil conditions, as well as their effectiveness to nodulate legumes such as soybeans. Factors such as soil properties and legume species influence the volume and symbiotic effectiveness of native rhizobia to nodulate crop legumes. To investigate the abundance of rhizobia isolates, legume crops were uprooted to obtain nodules for most probable number (MPN) determination of rhizobia isolates, and soybean (Glycine max.) was used to verify the presence of suitable and efficient rhizobia strains for nitrogen fixation. Soil samples were obtained from the holes out of which nodules were collected, and the laboratory analysis included pH, Mg, K, available P, organic C, Ca, and N to establish the correlation between the soil status and number of rhizobia isolates' cells. Significant variations (p-value <.05) were observed in the cell counts of Rhizobia isolates from Glycine max, Phaseolus vulgaris, Pisum sativum, and Vigna unguiculata, particularly when compared to Arachis hypogaea isolates under acidic conditions. Notably, Pisum sativum and Vigna unguiculata showed consistent performance across all pH conditions. The number of rhizobia isolates was found to be significantly linked to total N and P deficiencies (p < .05). It was also established that total N was dependent on the number of rhizobia cells and that there is a strong correlation between organic carbon and N content. This study highlights the crucial role of understanding and optimizing conditions for rhizobia nodulation in diverse soil environments, emphasizing its potential impact on enhancing biological nitrogen fixation in legumes.